2017
DOI: 10.1161/jaha.117.007229
|View full text |Cite
|
Sign up to set email alerts
|

Relative Survival After Transcatheter Aortic Valve Implantation: How Do Patients Undergoing Transcatheter Aortic Valve Implantation Fare Relative to the General Population?

Abstract: BackgroundTranscatheter aortic valve implantation (TAVI) is indicated for patients with aortic stenosis who are intermediate‐high surgical risk. Although all‐cause mortality rates after TAVI are established, survival attributable to the procedure is unclear because of competing causes of mortality. The aim was to report relative survival (RS) after TAVI, which accounts for background mortality risks in a matched general population.Methods and ResultsNational cohort data (n=6420) from the 2007 to 2014 UK TAVI r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Although TAVI is a less invasive treatment than aortic valve replacement, TAVI itself has several risks, such as hemorrhage with vascular damage, embolic stroke, severe conduction abnormalities with left bundle branch block, or complete AV block, paravalvular leakage, and infective endocarditis [15]. However, the relative survival after TAVI is high, and survival rates in those aged > 85 years are approximately those of a matched general population within 3 years [3]. TAVI does not seem to bear an increased risk for patients with CKD stage G3-5 [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TAVI is a less invasive treatment than aortic valve replacement, TAVI itself has several risks, such as hemorrhage with vascular damage, embolic stroke, severe conduction abnormalities with left bundle branch block, or complete AV block, paravalvular leakage, and infective endocarditis [15]. However, the relative survival after TAVI is high, and survival rates in those aged > 85 years are approximately those of a matched general population within 3 years [3]. TAVI does not seem to bear an increased risk for patients with CKD stage G3-5 [4].…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter aortic valve implantation (TAVI) has revolutionized the treatment of high-risk patients with severe AS. The relative survival after TAVI is high, and survival rates in those aged > 85 years are approximately those of a matched general population within 3 years [3]. TAVI is feasible in patients with not only chronic kidney disease (CKD) stage G3-5 [4] but also CKD stage G5D [5].…”
Section: Introductionmentioning
confidence: 99%
“…6 In a study analyzing the mortality rate in 6,420 patients undergoing TAVI (UK registry) compared to a matched general population, it was found that relative survival after TAVI was high, corresponding to 95.4%, 90.2%, and 83.8% at 30 days, 1 year, and 3 years, respectively. 7 Increasing age was associated with significantly lower excess hazards after TAVI, with survival rates in patients ages > 85 years approximated those of a matched general population within 3 years. In view of current evolution, it is thus very likely that TAVI will progressively supplant SAVR for AS patients who are eligible for both procedures.…”
mentioning
confidence: 92%
“…This observation might corroborate the data from the CENTER collaboration study showing that patients with stroke had more frequently documented new-onset atrial fibrillation. 7 Similarly, as in the VISTA-16 study on ACS patients, 17 it would be interesting to determine if, in addition to initial hsCRP level, serial monitoring of hsCRP levels post-TAVI could further help identify patients at greater risk of postprocedural cardiovascular events or death, both on the short and long term. In TAVI patients, it remains to be determined whether hsCRP level represents a surrogate marker of inflammation or whether it should be considered as a direct biological target.…”
mentioning
confidence: 99%
“…Subsequently, the duration of hospitalization was also lower in TAVI group as compared to SAVR group (eight days vs. 12 days, p< 0.001) [ 12 ]. Since TAVI involve high-risk patients, so all cause 30 days, one year and three years observed survival estimates are lower, which are 94.7%, 83.4% and 64.5%, respectively [ 13 ].…”
Section: Introductionmentioning
confidence: 99%